Mapping Distribution Approach in Various Types of Use Sub-Optimal Dry Land in Aceh Besar District. Issue 1 (March 2021) - Umar, H A; Sufardi, S; Syafruddin, S; Arabia, T
Abstract: Sub-optimal land can be defined as land that naturally has low productivity due to internal (intrinsic) factors such as parent material, physical, chemical, and biological properties of soil, and external factors such as rainfall and extreme temperatures. For that reason, it is necessary to map foreknow the various types of sub-optimal dry land uses and their size in the district Aceh Besar. Administration maps, land use maps, slope maps, and soil type maps would later be overlaid and digitized on the screen to obtain the map and the area of research to be carried out. The slope gradient was limited to only 25% due to looking conditions that allow it to be used in the management business agriculture. The forest area was 19, 136.65 ha, the dry land agricultural area was 89, 472.15 ha, area open land of 1, 070.75 ha, and scrub area of 58, 840.87 ha. It can be observed that land use in the Aceh Besar district is dominated by Dryland farming.